A brief review of the 2d/4d correspondences*This is a contribution to the review issue 'Localization techniques in quantum field theories' (ed Pestun and Zabzine) which contains 17 chapters available at [001]. (13th October 2017) - Tachikawa, Yuji
Abstract: An elementary introduction to the 2d/4d correspondences is given. After quickly reviewing the 2d q -deformed Yang–Mills theory and the Liouville theory, we will introduce 4d theories obtained by coupling trifundamentals to SU(2) gauge fields. We will then cleraly see that the supersymmetric partition function of these theories on S 3 × S 1 and on S 4 is given, respectively, by the q -deformed Yang–Mills theory and the Liouville theory. After giving a short discussion on how this correspondence may be understood from the viewpoint of the 6d N = ( 2, 0 ) theory, we conclude the review by enumerating future directions. Most of the technical points will be referred to more detailed review articles.